2020
DOI: 10.4103/jfmpc.jfmpc_1207_19
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Leukocyte Esterase Reagent Strip (LERS) test for rapid bedside screening of spontaneous bacterial peritonitis: An observational study

Abstract: Introduction: Spontaneous bacterial peritonitis (SBP) is a frequent and severe complication in cirrhotic patients with ascites. SBP is generally diagnosed based on an increased number of polymorphonuclear neutrophils in the ascitic fluid (>250/mm 3 ) and positive culture. Usually fluid analysis and culture take time and precious hours are lost in starting therapy. Leukocyte Esterase Reagent Strips (LERS) have consistently given a high negative predictive value (>95% in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In a study by Khairnar et al 14 done in 64 patients, 17 with SBP, using multistix 10SG (Siemens India), had shown the sensitivity, specifi city, PPV, NPV and accuracy of 100, 94, 57, 100 and 94.5 percent with cut-off grade 2 (:125 PMNL/ mm 3 ) and 76.4, 100, 100, 92.1 and 93.7 percent respectively with grade 3 (:500PMNL/mm 3 ) as cut-off. The fi nding in this study showed high sensitivity and NPV with low specifi city for grade 2 as cut-off and specifi city and PPV improved at cost of sensitivity for grade 3 as cut-off and these fi nding are similar to our study.…”
Section: Discussionmentioning
confidence: 98%
“…In a study by Khairnar et al 14 done in 64 patients, 17 with SBP, using multistix 10SG (Siemens India), had shown the sensitivity, specifi city, PPV, NPV and accuracy of 100, 94, 57, 100 and 94.5 percent with cut-off grade 2 (:125 PMNL/ mm 3 ) and 76.4, 100, 100, 92.1 and 93.7 percent respectively with grade 3 (:500PMNL/mm 3 ) as cut-off. The fi nding in this study showed high sensitivity and NPV with low specifi city for grade 2 as cut-off and specifi city and PPV improved at cost of sensitivity for grade 3 as cut-off and these fi nding are similar to our study.…”
Section: Discussionmentioning
confidence: 98%